2018
DOI: 10.1002/cbic.201800050
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Encoded Ratiometric pH Probe: Wavelength Regulation‐Inspired Design of pH Indicators

Abstract: Mutants of human cellular retinol-binding protein II (hCRBPII) were engineered to bind a julolidine retinal analogue for the purpose of developing a ratiometric pH sensor. The design relied on the electrostatic influence of a titratable amino acid side chain, which affects the absorption and, thus, the emission of the protein/fluorophore complex. The ratio of emissions obtained at two excitation wavelengths that correspond to the absorption of the two forms of the protein/fluorophore complex, leads to a concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Engineering of hCRPBII combined with the use of a julolidine retinal analog further allowed the development of a ratiometric pH sensor. [80] The sensor takes advantage of the sensitivity of the bound chromophore to the electrostatic environment within the binding cavity. The absorption profile changes as a function of the protonation state of a carboxylic side chain in proximity of the bound iminium.…”
Section: Covalent Fluorogenic Labelingmentioning
confidence: 99%
“…Engineering of hCRPBII combined with the use of a julolidine retinal analog further allowed the development of a ratiometric pH sensor. [80] The sensor takes advantage of the sensitivity of the bound chromophore to the electrostatic environment within the binding cavity. The absorption profile changes as a function of the protonation state of a carboxylic side chain in proximity of the bound iminium.…”
Section: Covalent Fluorogenic Labelingmentioning
confidence: 99%
“…The presence of a titratable functional group close to the chromophore binding pocket renders both the absorption and fluorescence emission sensitive to pH change. [97] Fluorescent chemogenetic reporters can also be used creatively to generate new types of biosensors. By coupling chemogenetic reporters with a sensing domain, it is possible to condition the fluorogen binding (and thus fluorescence) to the recognition of the analyte.…”
Section: Biosensorsmentioning
confidence: 99%
“…Human cellular retinol binding protein II (hCRBPII) chaperones both retinol and retinal within the cell. Our group has engineered these templates to create rhodopsin mimics used to understand protein‐based absorption tuning, protein‐directed photoisomerization pathways, [35–37] new classes of fluorescent and photoswitchable fluorescent protein tags, [38] and pH sensors [39,40] . We recently reported that some variants of hCRBPII give rise to domain‐swapped (DS) dimers [41] .…”
Section: Figurementioning
confidence: 99%
“…Our group has engineered these templates to create rhodopsin mimics used to understand protein-based absorption tuning, protein-directed photoisomerization pathways, [35][36][37] new classes of fluorescent and photoswitchable fluorescent protein tags, [38] and pH sensors. [39,40] We recently reported that some variants of hCRBPII give rise to domain-swapped (DS) dimers. [41] We then exploited the hCRBPII DS dimer as a design template to engineer a new class of protein conformational switches, activated by ligand binding or environmental reduction potential, characteristics lacking in the monomeric fold of the protein.…”
mentioning
confidence: 99%